Analisis Kemampuan Keruangan Ditinjau Dari Motivasi Belajar Pada Pokok Bahasan Bangun Ruang Sisi Datar - Anggreani, Seruni; Dori Lukman Hakim (Absis: Mathematics Education Journal, 2025)
This study aims to describe students' spatial geometry abilities in terms of their learning motivation and to detail the achievement of each indicator of students' spatial abilities. The research method used is descriptive qualitative. Data collection techniques in this study include written tests, simple interviews, and observations. The research was conducted with 35 students, from which 6 students were selected based on certain characteristics: high, medium, and low. The spatial ability test results of these 6 students were then analyzed in relation to their learning motivation. The results of the study indicate that high learning motivation can significantly influence students' geometry skills, particularly their spatial abilities. This means there is a correlation between spatial ability and students' learning motivation, where students with high motivation tend to have a stronger drive and need for learning.